Factor structure of the comprehensive preparedness of shooters 14-15 years old, specializing in shooting from classic bow - I.M. Sobko; A.L. Kovtun; L.O. Ulaeva (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The purpose of the work: to determine the factor structure of the complex preparedness of shooters of 14-15 years who specialize in the Classic bow, for rational construction of the training process of athletes of this age category. Material and methods. The experiment was attended by 16 bow-shooters (girls) aged 14-15 years old, specializing in Classic bow, sport school "Avangard" in Kyiv. The experiment was conducted in the preparatory period, September 2018. The archers were tested for physical fitness (shuttle running 4x9m, push-ups 30 s, jumping with skipping-rope, running 30 m, Romberg test, hanging on bent hands at an angle of 90˚, jump in length from place, raising the torso to a sitting position, dynamometry of the right and left hands), technical preparedness (holding the bow in the "stretch", archery 18 m, archery 60 m, stretching the bow on the right and left hand for 30 s). The obtained data were processed mathematically using factor analysis methods. Results. The factor structure of physical and technical preparedness of shooters, which are at the stage of specialized basic training, is established. Five factors were identified: static power endurance, dynamic power endurance, coordination capabilities, speed capabilities, strength capabilities. Conclusions. It is revealed that the most important indicators of the complex training of archers 14-15 years old are the indicators of shooting in the open air and indicators of the static strength of the archer, as well as indicators of shooting in the room and indicators of the dynamic endurance of the archer, indicating the dependence of physical and technical training. The use of rational means and methods of physical and technical training in the training process of athletes is recommended.